2023
DOI: 10.1002/pc.27304
|View full text |Cite
|
Sign up to set email alerts
|

Healable carbon fiber reinforced epoxy composites: Synchronous healing of matrix and interface damage

Abstract: Thermosetting composites are a range of high‐performance materials with important applications in multiple fields. However, inaccessible damage such as microcracks ingress from the environment may appear with long term use. Over time, the micro‐damage further expands and leads to material failure. The damage includes the interface damage and the matrix damage. Therefore, the healing technology of composites needs to respond and heal the micro‐damage of the interface and resin in the composites synchronously. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…As a thermoset matrix for advanced engineering composites, epoxy resin (EP) exhibits a range of excellent properties, including high tensile strength, excellent dimensional stability, and good chemical resistance. [1][2][3] Today, EP materials are widely used in automotive, aviation, rail transportation, and construction. [4][5][6][7] However, neat EP suffers a lot from its brittleness, fatigue resistance, and poor tribology behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As a thermoset matrix for advanced engineering composites, epoxy resin (EP) exhibits a range of excellent properties, including high tensile strength, excellent dimensional stability, and good chemical resistance. [1][2][3] Today, EP materials are widely used in automotive, aviation, rail transportation, and construction. [4][5][6][7] However, neat EP suffers a lot from its brittleness, fatigue resistance, and poor tribology behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Due to their exceptional specific strength and stiffness, carbon fiber reinforced composites in particular have become a study focus in the disciplines of aerospace and marine engineering in recent years. [5][6][7] Poly(ether-ether-ketone) (PEEK), a special engineering polymer material with good solvent resistance. 8 PEEK and PEEK composites also have well-known biocompatibility, inherent radiolucency, and chemical resistance, making them potential implant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their superior all‐around properties, fiber reinforced polymer matrix composites are a good substitute for traditional homogeneous materials such as metals and ceramics 1–4 . Due to their exceptional specific strength and stiffness, carbon fiber reinforced composites in particular have become a study focus in the disciplines of aerospace and marine engineering in recent years 5–7 . Poly(ether‐ether‐ketone) (PEEK), a special engineering polymer material with good solvent resistance 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] However, because of the low matrix toughness and the poor interfacial interaction between fiber and matrix, FRPs are more susceptible to defects and damages, leading to rapid growth cracks and the delamination behaviors and shortening the service life of FRPs. [11][12][13] Therefore, improving the interlaminar shear strength (ILSS) of FRPs and healing the damage are key issues for enhancing the service life of composites. [14][15][16][17][18][19][20] Previous studies have shown that developing a nanoparticle-modified matrix with improved toughness can enhance the mechanical properties of FRPs, 21 since the matrix is a key component of composites that can dominate the toughness of FRPs.…”
Section: Introductionmentioning
confidence: 99%